209k views
4 votes
What is the answer to this problem, step by step
7 – (5t – 13) = –25

2 Answers

2 votes
The answer is t = 9 because you start with distributing the parentheses then you add 7 and 14 then you bring the sum of that over to the other side but with the opposite sign then you divide whatever numbers in front of the variable and then that’s your answer
User Miro Kropacek
by
5.6k points
3 votes
7

(
5
t

13
)
=

25
(Expand

(
5
t

13
)
)
7

5
t
+
13
=

25
(Simplify the equation)
20

5
t
=

25
(Minus
20
on both sides)

5
t
=

45
(Divide by

5
on both sides)
Answer-
t
=
9
User Aegenes
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.